Заходи громадської дипломатії іноземних держав як засіб впливу на масову аудиторію в Україні - Сухорольська, Ірина (Видавництво Львівської політехніки, 2014)
Охарактеризовано засади громадської дипломатії, яка здійснюється стосовно іноземної масової аудиторії. Розглянуто спектр заходів громадської дипломатії США, Великобританії, Німеччини, Росії щодо широких верств населення в Україні, визначено особливості такої діяльності. The paper deals with the Public Diplomacy instruments such as international information programmes, international broadcasting, cultural diplomacy aimed at mass audience. Since the time when the concept of public diplomacy was developed and implemented in the United States Ukraine has become its target audience. During the period of Cold War such activity of the Western powers was aimed at breakthrough of information blockade and served as a counteraction to Soviet propaganda. The collapse of the Soviet Union and establishment of Ukrainian independence resulted in growth of foreign players influencing Ukrainian audience. Their activity is getting more complex and diverse in the information society. The activity of the USA, Great Britain, Germany, and Russia towards the Ukrainian audience is analyzed in the article. The Public Diplomacy instruments of Western countries aimed at building democracy and civil society in Ukraine are thoroughly analyzed. The author makes comparison of Western and Russian practices of Public Diplomacy which resulted in pointing out the purpose of such activities. Special attention is paid to studying the Russian foreign information policy towards Ukraine and its specific target audience in the former Soviet Union. The ideas for improving relations between two countries are presented. The sources of the research include official websites of governments, ministries of foreign affairs, foreign embassies in Ukraine, special Public Diplomacy institutions (the British Council, Rossotrudnichestvo, Goethe-Institute), international broadcasters (BBC, Voice of America, Radio Free Europe/Radio Liberty, Deutsche Welle, Russia Today), other web portals related to the government institutions.
Foreign public diplomacy instruments as a tool of influence on mass audience in Ukraine
Keywords: громадська дипломатія; публічна дипломатія; масова аудиторія; інформаційні програми; міжнародне телерадіомовлення; культурна дипломатія; public diplomacy; mass audience; international information programmes; international broadcasting; cultural diplomacy